IMPLEMENTASI KEBIJAKAN PENILAIAN NASIONAL: TINJAUAN LITERATUR SISTEMATIS - Istha Herlitha; Sirajuddin Saleh; Lala Vitaloka; Evi Kurnia Kadir; Amin Rais; Mega Purnama; Sabbi Hisma (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze development trends, thematic structures, and scientific collaboration patterns in the research on national assessment policy implementation through a systematic literature review approach. The primary focus of this research is to identify the dynamics of scientific publications, knowledge structures, and dominant actors in the development of national assessment policy research within a global context. The research method employs a bibliometric approach using VOSviewer and Biblioshiny software to analyze publication data that has undergone a screening process, resulting in 35 articles that met the inclusion criteria. The analysis was conducted across three main dimensions: Annual Scientific Production and Most Relevant Sources to examine publication trends, keyword co-occurrence analysis to map the thematic structure, and author and country collaboration analysis to understand knowledge production networks. The findings indicate that the study of national assessment policy implementation experiences fluctuating growth with a significant increase in the final period, dominated by themes such as PISA, OECD, and large-scale assessment. Furthermore, the study reveals an imbalance in author and country contributions, with developed nations remaining the dominant actors in knowledge production. In conclusion, this research underscores that the implementation of national assessment policies is evolving within a framework of global education governance, which is heavily influenced by the logic of standardization, educational datafication, and global knowledge structure inequalities. Keywords: assessment, policy, evaluation, governance, education